Characterization of non-disabling sensorimotor deficits induced by mild traumatic brain injury in rats - Fuente, Sofía de la (2022)
Fil: Fuente, Sofía de la. Universidad Nacional de Córdoba. Facultad de Ciencias Quimicas. Instituto de Farmacologia Experimental de Córdoba; Argentina.